ECDD-S16, a synthetic derivative of cleistanthin A, suppresses pyroptosis in Burkholderia pseudomallei-infected U937 macrophages - Suphasuta Khongpraphan; Sucharat Sanongkiet; Chularat Luangjindarat; Sarut Thairat; Bumrung Munyoo; Napason Chabang; Sitthivut Charoensutthivarakul; Suparerk Borwornpinyo; Patoomratana Tuchinda; Marisa Ponpuak; Pongsak Utaisincharoen; Matsayapan Pudla (PLoS ONE, 2025)
Background Melioidosis is an infectious disease caused by an intracellular Gram-negative bacterium, Burkholderia pseudomallei, which is a common cause of community-acquired sepsis in Southeast Asia and Northern Australia. The mortality rate in acute melioidosis patients, which is caused by sepsis, is very high (47.1%). Therefore, reducing inflammation may lead to the treatment of patients with acute melioidosis. Previously, ECDD-S16 was reported to be a potential compound for inhibiting inflammatory cell death (pyroptosis). Objective In this study, we further investigated the involvement of ECDD-S16 in pyroptosis induced by B. pseudomallei in the U937 human macrophage cell line. Methods To investigate the biological activity of ECDD-S16, U937 macrophages were infected with B. pseudomallei before treatment with the compound. The expression of pyroptosis marker was determined by lactate dehydrogenase (LDH) assay, western blotting and ELISA assay. Additionally, the intracellular growth of B. pseudomallei was examined by CFU determination. Furthermore, colocalization of the bacteria with phagosome acidification was observed by immunofluorescent staining. Results The results showed that ECDD-S16 decreased LDH release and levels of pyroptosis-related proteins in B. pseudomallei-infected cells by inhibiting phagolysosome acidification. Moreover, the attenuation of pyroptosis did not interfere with the intracellular survival of B. pseudomallei in U937 macrophages. Conclusion Our findings indicated that ECDD-S16, a novel compound, interferes with caspase-1/4/5 activation, which may lead to the prevention of sepsis in acute melioidosis patients.